High-frequency low-power local oscillator generation - Miao, Yannan (2012)
With rapid development in the area of RF and wireless communication, the interest in frequency synthesizers has grown rapidly in the last few years. Frequency synthesizer is used for local oscillator (LO) generation. In this thesis, our aim is to explore high-frequency low-power LO generation in CMOS technology. We focus on three most power-hungry blocks in a frequency synthesizer, which dominate the total power consumption due to their high-frequency operation, namely voltage-controlled oscillator (VCO), frequency divider and frequency multiplier, as these circuits are the bottleneck to achieve the above mentioned aim. Through reducing their power consumption, the total power consumption of the frequency synthesizer can be reduced significantly. Moreover, the phase noise of the frequency synthesizer is significantly dependent on the VCO and the frequency multiplier. Thus, novel ideas for these circuits are proposed in Chapter 3, Chapter 4 and Chapter 5. Finally, these ideas are implemented in a frequency synthesizer as a design example in Chapter 6. The frequency synthesizer can operate at the 24-GHz Instrument, Scientific and Medical (ISM) band, which can be used for automotive short range radar. With these ideas in these proposed circuits, the proposed frequency synthesizer can have better performances than those previous designs.